2017
DOI: 10.1111/ocr.12160
|View full text |Cite
|
Sign up to set email alerts
|

In silico and functional evaluation of PTH1R mutations found in patients with primary failure of eruption (PFE)

Abstract: PTH1R mutations identified in PFE likely result from diminished function due to truncation of the protein, lack of efficient G-protein interactions and putatively attenuated signal transduction. By identifying the mode of protein dysfunction, scientist-clinicians are better prepared to recognize and thereby develop improved methods of treatment, starting at the molecular level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 16 publications
0
6
0
1
Order By: Relevance
“…While substitution of Arg-147 in the extracellular domain of the receptor partially affected binding of PTH 1-34 and cAMP production, the substitution of Arg-383 with Gln (R383Q) had little effect on the binding of the ligand. The partial suppression of cAMP production in HeLa cells with R383Q-PTH1R is considered to be due to other reasons, such as possible alteration in G-protein binding (Hendricks et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…While substitution of Arg-147 in the extracellular domain of the receptor partially affected binding of PTH 1-34 and cAMP production, the substitution of Arg-383 with Gln (R383Q) had little effect on the binding of the ligand. The partial suppression of cAMP production in HeLa cells with R383Q-PTH1R is considered to be due to other reasons, such as possible alteration in G-protein binding (Hendricks et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The proband was a 13-year-old young man with an incomplete eruption of the right upper anterior tooth (11,12,13), resulting in a signi cant open-bite. His left rst molar 26 partially erupted.…”
Section: Case Presentationmentioning
confidence: 99%
“…The clinical examination revealed that the right maxillary anterior teeth of the proband (11,12,13) were below the occlusion plane, forming an open-bite of 4mm. The eruption height of the left maxillary rst molar (26) was slightly insu cient.…”
Section: Clinical Analysis Of the Probandmentioning
confidence: 99%
See 1 more Smart Citation
“…The etiology of missing teeth, that is, a disturbance of tooth development (i.e., tooth agenesis or disturbance of tooth eruption), especially of the permanent teeth, remains unknown. The etiology of tooth agenesis includes genetic factors, environmental factors, or a combination thereof [9,10,11,12], while the etiology of a disturbance of tooth eruption may include systemic factors, local factors, as well as genetic factors [13,14,15,16]. For example, prolonged retention of a deciduous tooth due to failure of deciduous tooth resorption, abnormal an eruptive path, the presence of a supernumerary tooth, or anomalous position of a tooth (e.g., tilting, displacement, transmigration), can disturb the eruption of permanent teeth.…”
Section: Introductionmentioning
confidence: 99%